2010
DOI: 10.1097/qai.0b013e3181f0ccb6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Transmission Risk Behavior of Adolescents With HIV Acquired Perinatally or Through Risky Behaviors

Abstract: To limit HIV transmission and prevent unplanned pregnancies, developmentally appropriate risk-reduction interventions, and screening and treatment referral for sexual abuse, must be integrated into the care of both perinatally and behaviorally HIV-infected adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 26 publications
2
42
2
Order By: Relevance
“…He also noted that these rates are similar to the prevalence reported for high school youth with similar demographic backgrounds. Koenig et al surveyed HIV infected boys and girls, 47% reported a history of unprotected intercourse since their sexual debut (12 perinatal and 37 behavioral), again the average age was 14 [19]. Our findings and the results of previous publications reinforce that adolescents would benefit from further support and sexual health interventions to improve and optimize condom usage so as to reduce the risk of transmission.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…He also noted that these rates are similar to the prevalence reported for high school youth with similar demographic backgrounds. Koenig et al surveyed HIV infected boys and girls, 47% reported a history of unprotected intercourse since their sexual debut (12 perinatal and 37 behavioral), again the average age was 14 [19]. Our findings and the results of previous publications reinforce that adolescents would benefit from further support and sexual health interventions to improve and optimize condom usage so as to reduce the risk of transmission.…”
Section: Discussionsupporting
confidence: 78%
“…LNG: Levonorgestrel-Releasing Intrauterine System (Mirena®), ENG: Etonogestrel Implant (Nexplanon or Implanon®), DMPA: Depot Medroxyprogesterone Acetate COC combined oral contraceptive, Patch (Ortho Evra®), Ring (Nuva Ring®) Condoms were the primary contraceptive; persons who used condoms for dual protection are listed according to the hormonal contraceptive utilized. [4,10,11,[17][18][19][20]. Tassiopoulos noted that 28% of perinatally infected adolescents 10 to 18 years of age (males and females) reported sexual intercourse, 62% had recent intercourse without a condom, and the median age of sexual debut was 14 years of age [20].…”
Section: Discussionmentioning
confidence: 99%
“…As in studies in other populations, older age was a significant predictor of behavioral health risks for both HIV-infected and HIV-exposed youth. 22 Also, among PHIV + youth, those with biological mother as the primary caregiver were over three times more likely to have two or more comorbidities than those with a relative or nonrelative primary caregiver. The stress of maternal illness, including birth mothers' own comorbid health, mental health, or substance abuse conditions, 3,43 may compound the effects of the youth's own HIV infection.…”
Section: Mellins Et Almentioning
confidence: 99%
“…Youth with behaviorally acquired HIV, who share high levels of mental health problems, nonadherence, and sexual risk behaviors, may differ substantially from youth with perinatal HIV exposure in that they are considerably older when first infected and have already engaged in sexual and/or drug risk behavior leading to HIV infection. [20][21][22] Perinatally HIV-exposed, but uninfected (PHEU) youth have been considered a more appropriate peer comparison group because, with the exception of HIV infection, they share many sociodemographic characteristics, as well as exposure prenatally and postnatally to maternal HIV infection. 7 Moreover, given the growing population of perinatally HIV-exposed but uninfected youth in the United States and globally, understanding their psychosocial functioning is an important public health goal in its own right.…”
mentioning
confidence: 99%
“…These theories have been taken up in global public health literature grappling with the health-related behaviors of young people growing up with chronic illnesses such as HIV (Valencia and Cromer 2000;Koenig et al 2010). This can have the effect of casting aspects of young people as inherently problematic, an approach which is compounded by an increasing focus on the management of HIV as a chronic condition like "any other" (Moyer and Hardon 2014) and on individual responsibility in the context of HIV treatment and transmission more generally (Paparini and Rhodes 2016).…”
mentioning
confidence: 99%